MARKETING STRATEGY PT. MIGHTY IVORY IN THE INDONESIAN AUTOMOTIVE INDUSTRY - Qintan Mudaningrum; Prima Mulyasari (Jurnal Scientia, 2023)
In this study aiming to determine PT Gading Prima Perkasa's marketing strategy, researchers used a qualitative approach using Grounded Theory, which aims to explore the extent of Honda Bintaro's marketing strategy. The data used for this research are primary data and secondary data. Taking into account the situation analysis obtained from all external and internal factors, there are several categories and themes that are discussed in this research. From these results it is known that what are Honda Bintaro's marketing strategies through internal and external factors. The next stage is to pay attention to the suitability between the existing Honda Bintaro Segmentation, Position and Target with the analysis of the situation and position obtained, so that appropriate marketing strategies can be prepared and determined. Honda Bintaro is unique in promoting its products so that it can compete with newcomers